1
$\begingroup$

Denote by $B_n$ the Bernoulli sequence (defined by the exponential generating function $\frac{x}{e^x-1}=\sum_{n=0}^{\infty}\frac{B_n}{n!}x^n$). As we know $$ \sum^{n}_{j=0}\binom{n}{j}B_j=B_n\; ; \; n\geq 2 $$ what about $\sum^{n}_{j=0}(-1)^j\binom{n}{j}B_j$, and as a more general case $$ \sum^{n}_{j=0}\frac{(-1)^{j+1-k}}{j+1}\binom{n}{j}\binom{j+1}{k}B_{j+1-k} $$ where $k$ is a given integer such that $1\leq k\leq n+1$ (is there any similar identity?).

Note that putting $k=1$ we get the first summation.

$\endgroup$
  • 2
    $\begingroup$ All $B_{2k+1}$, except $B_1$ are $0$. So you get $B_n - 2nB_1$. $\endgroup$ – Daniel Fischer Nov 5 '16 at 17:51
2
$\begingroup$

Suppose we have the Bernoulli numbers defined by

$$\frac{z}{\exp(z)-1} = \sum_{n\ge 0} B_n \frac{z^n}{n!}$$

and ask about a closed form for the quantity

$$\sum_{j=0}^n \frac{(-1)^{j+1-k}}{j+1} {n\choose j} {j+1\choose k} B_{j+1-k} \\ = \sum_{j=k-1}^n \frac{(-1)^{j+1-k}}{j+1} {n\choose j} {j+1\choose k} B_{j+1-k}.$$

This is

$$\frac{1}{k} \sum_{j=k-1}^n (-1)^{j+1-k} {n\choose j} {j\choose k-1} B_{j+1-k}.$$

Now we have

$${n\choose j} {j\choose k-1} = \frac{n!}{(n-j)! (k-1)! (j+1-k)!} = {n\choose k-1} {n+1-k\choose n-j}$$

so we get

$$\frac{1}{k} {n\choose k-1} \sum_{j=k-1}^n (-1)^{j+1-k} {n+1-k\choose n-j} B_{j+1-k} \\ = \frac{1}{k} {n\choose k-1} \sum_{j=0}^{n+1-k} (-1)^{j} {n+1-k\choose n+1-k-j} B_{j} \\ = \frac{1}{k} {n\choose k-1} \sum_{j=0}^{n+1-k} (-1)^{j} {n+1-k\choose j} B_{j}.$$

We thus obtain the closed form

$$\frac{1}{k} {n\choose k-1} \times (n+1-k)! [z^{n+1-k}] \exp(z) \frac{z}{1-\exp(-z)}.$$

This is

$$\bbox[5px,border:2px solid #00A000]{\frac{n!}{k!} [z^{n+1-k}] \frac{z \exp(z)}{1-\exp(-z)}.}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.